Analisis Penambahan Investasi Pada PT. XYZ dalam Pegembangan Usaha - Beatrix Tandi Rerung (RJABM (Research Journal of Accounting and Business Management), 2017)
This study aims to analyze the feasibility of additional investment for the company and application of investment feasibility analysis method relating to additional business activities at PT.PXY. The method used in analyzing the feasibility of additional investment is done by  several methods, namely Accounting Rate of Return (ARR) Method, Pay Back Period (PBP) Method, Net Present Value (NPV) Method, and Internal Rate of Return (IRR) The results show that the Company requires a fund of Rp. 1.162.799.000, - to add fixed assets in order to expand its operational activities. So the company's revenue will be bigger in the future. With the addition of fixed assets, the total value of fixed assets owned by PT. XYZ to Rp. 5.637.799.000, - for the project period of 2017 - 2021. With the addition of fixed assets and assumptions made may be valid for the life of fixed assets, the projected profit to be derived from additional fixed assets will be greater than the amount of profit generated fixed assets without additions. By using the net present value analysis, the addition of fixed assets is feasible to be executed because the present value of the net cash flow projection to be received from 2017 - 2021 has calculated the risk through certainty equivalent method so that net present value after addition is greater than without adding, Rp. 12.227.069.216, - is greater than Rp. 1.523.926.239, -. Keywords: Investment Method, Business